Building Collaborative Learning Through Lesson Study - *, Triyanto (Proceeding of International Conference on Teacher Training and Education, 2016)
Education in Indonesia is still experiencing a variety of complex problems. One problem is the poor quality of teaching. The low quality of learning is caused by lack of development system of quality learning in the classroom. Collaborative learning through lesson study can be a solution to improve the quality of learning in the classroom. This article discusses how to build a strategy of collaborative learning through lesson study. Teachers will work together and discuss and find solutions of problems in the classroom. Collaborative learning can improve the quality of learning and strengthen collegiality among teachers.